2021
DOI: 10.1002/ajh.26255
|View full text |Cite
|
Sign up to set email alerts
|

Persistent bone marrow minimal residual disease as a “high‐risk” disease feature in multiple myeloma

Abstract: curves: (A) shows the relapse free survival and (B) overall survival of persistent MRD positivity compared to those with sustained MRD negativity. (C) shows relapse free and ID overall survival when patients were stratified based on GEP70 score (HR vs. LR) CORRESPONDENCE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…More importantly, we show that MRD conversion from negative to positive confers a more favorable outcome compared with patient with persistent MRD positivity throughout the disease course. 31,32 In a subset of patients with serial MRD assessment from diagnosis, we noted an apparent paradox of early attainment of MRD negativity associated with an inferior clinical outcome. This is in agreement with previous publications showing that a precipitous response to induction therapy is an indicator of a more proliferative MM.…”
Section: Discussionmentioning
confidence: 73%
“…More importantly, we show that MRD conversion from negative to positive confers a more favorable outcome compared with patient with persistent MRD positivity throughout the disease course. 31,32 In a subset of patients with serial MRD assessment from diagnosis, we noted an apparent paradox of early attainment of MRD negativity associated with an inferior clinical outcome. This is in agreement with previous publications showing that a precipitous response to induction therapy is an indicator of a more proliferative MM.…”
Section: Discussionmentioning
confidence: 73%
“…However, it is still unclear of how to reach this goal, e.g., in patients who failed to achieve MRD negativity during standard treatment. Mohan et al 34 recently confirmed that persistent MRD positivity despite change in treatment is associated with inferior clinical outcome. Intensifying therapy may be a way to address this issue as carfilzomib/lenalidomide maintenance resulted in a superior rate of MRD‐negative patients compared to lenalidomide monotherapy in the FORTE trial (http://clinicaltrials.gov Identifier: NCT02203643) 35 .…”
Section: Discussionmentioning
confidence: 95%
“…4,15 MRD positivity particularly confers poor outcome in the setting of HR disease. 3,16 Our study population is enriched in HR disease (63%) with BM MRD positivity in all patients after ASCT1. Overall, there was augmentation of disease responses including attainment of MRD negativity in about 50% of patients after ASCT2 that translated into improved PFS.…”
Section: Tandem Autologous Stem Cell Transplantation In Patients With...mentioning
confidence: 99%
“…BM aspirate MRD assessment was performed using clinically validated 8-color flow cytometric analysis with a minimal sensitivity of 10 À5 cells 12,13 and was performed within 100 days of ASCT1 and ASCT2. 3 The median age at ASCT1 was 58 (interquartile range [IQR] 52-63) yrs with 40% (68/168) being female patients (Table S1). Black patients accounted for 16% (n = 26) of all patients.…”
Section: Tandem Autologous Stem Cell Transplantation In Patients With...mentioning
confidence: 99%